Traceability in Healthcare: Crossing Boundaries - Lovis, C. (Yearbook of Medical Informatics, 2008)
Objectives This paper is a survey on the problem of traceability in healthcare. Traceability covers many different aspects and its understanding varies among different players. In supply chains and retails, traceability usually covers aspects pertaining to logistics. The challenge is to keep trace of objects manufactured, to track their locations in a production and distribution processes. In food industry, traceability has received a lot of attention because of public health problems related to infectious diseases. For instance, in Europe, the challenge of traceability has been to build the tracking of meat, from the living animal to the shell. In the health sector, traceability has mostly been involved in patient safety around human products such as blood derivates contaminants or implanted devices and prosthesis such as mammary implants. There are growing interests involving traceability in health related to drug safety, including the problem of counterfeited drugs, and to privacy. Traceability is also increasingly seen as a mean to improve efficiency of the logistics of care and a way to better understand costs and usage of resources.Methods This survey is reviewing the literature and proposes a discussion based on the real use and needs of traceability in a large teaching hospital.Results and Conclusion Traceability in healthcare is at the crossroads of numerous needs. It is therefore of particular complexity and raises many new challenges. Identification management and entity tracking, from serialization of consumers’ good production in the supply chains, to the identification of actors, patients, care providers, locations and processes is a huge effort, tackling economical, political, ethical and technical challenges. New requirements are needed, not usually met in the supply chain, such as serialization and persistence in time. New problems arise, such as privacy and legal frameworks. There are growing needs to increase traceability for drug products, related to drug safety, counterfeited drugs, and to privacy. Technical problems around reliability, robustness and efficiency of carriers are still to be resolved. There is a lot at stakes. Traceability is a major aspect of the future in healthcare and requires the attention of the community of medical informatics.
Keywords: Traceability; identification management; logistics; supply chain; EPC; GS1